CONTRIBUTION OF ISLAMIC ACTIVITIES OF NURUL IKHWAN AND THE INTEREST OF READING AL-QUR'AN TO THE RESULTS OF STUDENT ISLAMIC EDUCATION SMP NEGERI 2 LUBUK PAKAM - Siti Halimah; Salamuddin Salamuddin; Imam Fadhilah Okyafyan (Universitas Dharmawangsa Medan, 2021)
This study aims to identify and describe: (1) the contribution of Nurul Ikhwan's Islamic spiritual activities to the learning outcomes of Islamic Religious Education of grade IX students at SMP Negeri 2 Lubuk Pakam, (2) the contribution of reading interest in the Qur'an on the learning outcomes of PAI class IX students at SMP Negeri 2 Lubuk Pakam, and (3) the contribution of Nurul Ikhwan's Islamic spiritual activities and the interest in reading the Koran to the learning outcomes of Islamic Religious Education students of grade IX at SMP Negeri 2 Lubuk Pakam. The research was conducted at Middle School 2 Lubuk Pakam. This research is a quantitative study with a correlation research method. The population in this study were all students of class IX which consisted of 9 classes with a total of 186. The sample was 20% of the students totaling 186, namely 37.2 rounded off by 37 students who were taken randomly (random sample). The data collection instrument used was a questionnaire. The data analysis used is correlation and regression. The findings of the study show: (1) there is a positive and significant contribution of spiritual activity to the learning outcomes of Islamic Education with a correlation number of 2.528 with the regression line equation Ŷ = 77.15 + 0.12 X1, (2) there is a positive and significant contribution of interest in reading Al-Qur ' the result of Islamic Religious Education learning with a correlation number of 3.591 with the regression line equation Ŷ = Ŷ = 66.26 + 0.27X2. and (3) there is a positive and significant contribution to spiritual activities and interest in reading Al-Qur'an on learning outcomes of Islamic Education with a correlation number of 14.42 with the regression line equation Ŷ = 35.56 + 0.09X1 + 0.24X2. The spiritual activity variable contributed to Islamic education learning outcomes by 10.70%, while the Qur'an reading interest variable contributed 22.90% to the Islamic Religious Education learning outcome.